OVERVIEW OF HEMOGLOBIN LEVELS IN PATIENTS WITH DIABETES MELLITUS Renal Complications in TOTO KABILA Hospital, 2020 - Puput Tilome; Torajasa Achmar; Yolan Dunggio (Journal of Health, Technology and Science (JHTS), 2021)
In 2018 the number of sufferersDiabetes mellitusin Bone Bolango district ranks sixth in Gorontalo Province. Data from Toto Kabila Hospital in 2020, as many as 24 patients. In some cases the disease that can cause complications in patients with diabetes mellitus is kidney failure. The decrease in hemoglobin levels in patients with kidney disorders is caused by decreased levels of erythropoietin which stimulates the bone marrow to produce red blood cells. The aim of the study was to describe the hemoglobin levels in patients with diabetes mellitus with kidney complications. This research design using quantitative descriptive. Conducted at Toto Kabila Hospital with a total sample of 24 patients with diabetes mellitus with kidney complications. The sampling technique was total sampling. Using the Univariate data analysis technique then the results are presented in tabular form. Based on the results of the study of 24 samples, it was found that the results of normal hemoglobin levels were 9 samples with a percentage (37.5%) while patients who had abnormal hemoglobin levels were 15 samples with a percentage (62.5%).